Molecular Methodology for the Detection of the Leishmania Genus in Different Biological Samples Extracted from Dogs - Ferreira de Sá, Ana Júlia Miranda; Araújo Olimpo, Lauren Laureanny; Royo, Vanessa de Andrade; de Melo Júnior, Afraino Farias; de Oliveira, Dario Alves; Campos Ferreira, Hanna Carolina; Azevedo, Alcinei Mistico; Menezes, Elytania Veiga (Acta Scientiae Veterinariae, 2019)
Background: The leishmaniases are a group of parasitic diseases caused by trypanosomatids belonging to the genus Leishmania, members of the class Kinetoplastida, order Trypanosomatidae, family Trypanosomatidae. Despite innumerous wild species that are infected, the domestic dog is a potential reservoir of Leishmania infantum in urban areas, which expands the transmission pathway to humans. When infected, the dog becomes Visceral Canine Leishmaniasis (CVL), which is characterized by a diverse clinical picture that ranges from asymptomatic to non-specific signs, such as skin lesions, lymphadenomegaly, weight loss, splenomegaly, and/or ocular lesions, thus impairing accurate and rapid diagnosis.In Brazil, it is considered a public health problem since it is endemic in certain regions. Therefore, parasitological, serological, and molecular methods can be used for the detection of the disease. However, the possibility of serological cross-reaction and the occurrence of co-infection with other trypanosomatids decreases the specificity rate to below 100%, which suggests the use of more accurate diagnostic tools. Several molecular targets and starting samples for leishmaniasis diagnosis are already standardized, but there is lack of data allowing the evaluation of the target, as well as which biological material is more efficient for the molecular diagnosis of CVL. The sensitivity of PCR may vary with DNA quality, primer type, parasitemia level, and number of target copies per cell. The spleen, blood, liver, aspirate of bone marrow and lymph nodes are the most frequently used for molecular diagnosis of CVL. The present study aimed to evaluate and compare three protocols of the polymerase chain reaction (PCR) for the molecular diagnosis of CVL in different biological samples removed from animals with different clinical and anatomopathological signs. Materials, Methods & Results: Fifty seropositive dogs for CVL were used, their clinical and anatomopathological signs were evaluated, and were classified as asymptomatic, oligosymptomatic, and polysymptomatic. The PCR was conducted with specific primers for each region of the smaller subunit of rRNA, ITS-1, and KDNA genes. The four types of biological samples (spleen, blood, lymph nodes, and liver) were analyzed. Among the 50 dogs studied, 19 (38%) were in the asymptomatic group; all the animals showed healthy appearance, 15/50 (30%) of the dogs presented up to two symptoms, being classified as oligosymptomatic. The polysymptomatic dogs [16/50 (32%)] presented with a compromised clinical status. The study showed that all dogs had a positive result in at least one analyzed PCR methodology. Comparing the results of the three types of tests in the four types of studied samples, the nested-PCR was the one which presented a greater frequency of amplifications. Of a total of 200 samples, 124 showed amplification, showing a 62% sensitivity. Discussion: The results revealed that, when 50 dogs were analyzed, the spleen tissue samples had a better performance in all the tests, but the sensitivity of blood samples was also satisfactory in Nested SSU rRNA-PCR and MC-PCR. The blood samples can be easily accessed with minimal invasion. One of the limitations around the use of biopsy of the spleen or its aspirate is the risk of serious bleeding or even death of the animal. Taking into consideration the practicality and because it has a lower grade of invasiveness, the combination of peripheral blood with Nested SSU rRNA-PCR becomes the methodology of first choice.